Propensity of Product Innovation in Malaysian Manufacturing Companies - Wan Jamaliah Wan Jusoh,; Nordin Mohd. Zain, (Asian Academy of Management Journal, 1999)
The significance of new product development (NPD) to corporate success has drawn numerous studies over the last forty years. (NICB 1964; Cooper 1979, 1980; Calantone and Cooper 1981 ; Booz, Alen and Hamilton 1982 ; Maidique and Zirger 1984 ; Cooper and Kleinschmidt 1986, 1987,1990). These studies have confirmed that new products are crucial to the financial well being of companies, making product development an inevitable function for most corporations.